CHALLENGES AFFECTING TEACHING OF CLOTHS DYEING TEXTILE DESIGN AS A COURSE IN SECONDARY SCHOOLS, KATSINA STATE, NIGERIA - Musa, Muntaka (PEOPLE: International Journal of Social Sciences, 2016)
This study is carried out to assess the challenges of teaching cloths dyeing in secondary schools in katsina state, Nigeria, aimed in finding out the students that are having interest in studying cloths dyeing, availability and quality of equipment for teaching and learning of cloths dyeing, possible challenges on teaching and learning cloths dyeing, as well as contributions of agencies in developing the subject. Secondary data is based on previous researches sourced in the libraries. The population of the study consists of all the staff and students of secondary schools offering cloths dyeing. A random sampling of all the staff (29) and 40% (384) of the students under cloths dyeing were selected for the research. A self structured 5 points Likert scale questionnaire containing 25 items was developed for collection of data; the data was analyzed using standard mean. The study comes up with findings as; students were studying the subject because they were compelled to or chose it themselves not by parental interest, colleague influence or pre-experience of chemical effects. The schools have laboratories with in adequate facilities, training materials and qualified teachers. The time allocated for practical is inadequate, and no provision made for Students Industrial Works Experience Scheme (SIWES). Parents were not visiting the schools during practical hours, the voluntary agencies were not contributing to the development of the subject, but the community and individuals were using dyed clothes for daily use and ceremonies. The researcher recommends proper orientation so that the government, voluntary agencies, communities and parents put hands together towards developing teaching and learning cloths dyeing in the affected secondary schools.